Une perspective philosophique sur la durabilité forte. Pour un écocentrisme relationnel - Rémi Beau (Développement Durable et Territoires)
The debate between strong and weak sustainability was often described by the environmental ethicists as a debate between economists to which they didn’t want to participate in. When criticizing the anthropocentric notion of « natural capital », environmental philosophers have defended that the goals of nature preservation needed to go far beyond the question of the sustainability of human societies. However, this criticism didn’t prevent some environmental ethicists from proposing a philosophical approach of ecological sustainability. We particularly analyse here some relational environmental ethics through the lenses of the debate on sustainability in order to define an ecocentric approach of strong sustainability.